INDONESIAN LOW-INCOME HOUSEHOLDS’ ACCEPTANCE OF MICROTAKAFUL IN EAST JAVA - Rapi, Muh Zul Hazmi; Kassim, Salina (Journal of Islamic Monetary Economics and Finance, 2023)
This research investigates the inclination of economically disadvantaged households in East Java, Indonesia, towards microtakaful adoption, utilizing an extended Theory of Planned Behavior (TPB). Analyzing data from 304 respondents through online and face-to-face surveys, the study reveals a significant demand for microtakaful among low-income households. Behavioral intention is positively influenced by factors such as attitude, subjective norms, price, and knowledge, with price being the most critical determinant. Notably, a substantial number of respondents from low-income backgrounds express positive intention toward microtakaful. The study underscores the importance of microtakaful providers raising awareness, offering affordable structures, and highlighting microtakaful's value as a risk management tool. By employing an advanced TPB model, this research offers profound insights into the perceptions and behavioral tendencies of East Java's low-income households regarding microtakaful. The findings suggest actionable strategies for providers to enhance outreach and participation among this vulnerable group, contributing to improved financial inclusion and resilience.